SPIA Update on Progress on 2019-2021 Workplan - CGIAR Standing Panel on Impact Assessment (CGIAR Advisory Services, 2020)
The SPIA 2019-2021 progress report seeks to provide a timely and relevant input into One CGIAR discussions and offer an update to SPIA stakeholders on the progress and ongoing activities of SPIA. The report describes studies in the pipeline, ongoing country-level data collection efforts, and details of initiatives at different levels to strengthen impact culture within the CGIAR.